An analytical study of modal dispersion characteristics of helically clad crystal-cored optical fiber - Mishra A.K.; Pandey P.C.; Kumar D.; Singh Ii O.N. (My University, 2025)
The uniaxial crystal cored optical fiber, with optical axis parallel to the fiber axis, having helical cladding is proposed and a characteristic equation is derived. Employing helical boundary conditions, the characteristic equation is found and dispersion curves are drawn for different Kco (the ratio of longitudinal and transverse refractive index) values and for different modal order ν. The field components in the core region of the proposed fiber are found and a curve between effective-index vs. normalized frequency is drawn. Our studies show that the anisotropic parameter (Kco) influences the dispersion characteristics and modal cut-offs and the modal grouping occurs at different V number for different Kco values. It is also observed that the helix pitch angle ψ has no any pronounced effect on propagation characteristics of the proposed fiber. © 2012 Elsevier GmbH. All rights reserved.